An integrated model for using social media applications in non-profit organizations. (April 2022) - Albanna, Hanaa; Alalwan, Ali Abdallah; Al-Emran, Mostafa
Abstract: The growing social media use worldwide has encouraged researchers to research on how and why it is adopted. However, the majority of studies have focused on the individual rather than the organizational level. There is also a relative paucity of research on organizational level factors that affect the use of social media applications by non-profit organizations (NPOs). Hence, this study aims to bridge this gap in research by analyzing the factors that determine social media use, which leads to increasing the effectiveness (i.e., awareness, community engagement, and fundraising) of NPOs. The data were collected through questionnaires distributed to public relations practitioners in 325 NPOs in Jordan and analyzed using structural equation modeling (SEM). The results supported the vital role of performance expectancy, effort expectancy, facilitating conditions, social influence, and management commitment on the actual usage of social media. The results also showed that using social media has a significant positive effect on awareness and community engagement, while no significant impact is reported regarding fundraising. Theoretically, this study extends the unified theory of acceptance and use of technology (UTAUT) by incorporating new factors, namely management commitment, awareness, community engagement, and fundraising, and proposing new relationships in the model. Practically, this research provides implications for stakeholders of NPOs, including policymakers and public relations practitioners. Highlights: Factors affecting the use of social media by NPOs. UTAUT is selected as a guiding theory to propose the theoretical model. UTAUT factors and management commitment impact social media use. Social media use influences awareness and community engagement. Social media use does not influence fundraising.